Методи вирішення задач динамічного розподілу спектра в системах когнітивного радіо - Коляденко, Ю. Ю.; Ткаченко, А. М. (ХНУРЕ, 2021)
In cognitive radio systems, it is customary to distinguish between primary and secondary users. The primary user owns the exclusive rights to use some licensed bandwidth. The secondary user has the right to use the licensed bandwidth only if it is not occupied by the primary user. Many different technical terms are used to describe spectrum allocation technologies among users. Although some of them are opposed to each other: dynamic spectrum access versus dynamic spectrum distribution, spectral range ownership versus free spectrum use, flexible spectrum access versus spectrum aggregation. The paper presents a classification of models of dynamic access to the spectrum used in the study and analysis of cognitive communication networks. The main methods for solving the problems of dynamic spectrum distribution are briefly considered.
Keywords: Когнітивне радіо; Розподіл спектра